1996
DOI: 10.1001/archsurg.1996.01430200071013
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation for Persistent or Recurrent Primary Hyperparathyroidism

Abstract: Repeated parathyroidectomy can be avoided in more than 95% of patients if an experienced surgeon performs bilateral cervical exploration during the initial parathyroid operation. For patients with persistent or recurrent primary hyperparathyroidism, preoperative localization studies and a focused surgical approach can result in a 95% success rate with minimum complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
154
4
11

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(177 citation statements)
references
References 12 publications
8
154
4
11
Order By: Relevance
“…23 Patients with multinodular thyroid disease, a short and thick neck or an adenoma in the retroesophageal, mediastinal or tracheoesophageal groove are more likely to yield a false-negative result. 24 Ultrasound is a sensitive investigation for intrathyroid glands, which account for 10% of ectopic glands, 13 and accurately identified one intrathyroid lesion prior to redo surgery in our series. Parathyroid glands are more readily identified when there is concordance between the sestamibi and US scans.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…23 Patients with multinodular thyroid disease, a short and thick neck or an adenoma in the retroesophageal, mediastinal or tracheoesophageal groove are more likely to yield a false-negative result. 24 Ultrasound is a sensitive investigation for intrathyroid glands, which account for 10% of ectopic glands, 13 and accurately identified one intrathyroid lesion prior to redo surgery in our series. Parathyroid glands are more readily identified when there is concordance between the sestamibi and US scans.…”
Section: Discussionmentioning
confidence: 57%
“…Ectopic glands have been found at redo surgery in the thymus, thyroid gland, tracheoesophageal groove or paraesophagus, mediastinum, carotid sheath, base of skull and lateral to the carotid artery. 13 The tracheoesophageal groove is the most common location of missed glands 14 and it has been suggested that a reluctance to dissect near the recurrent laryngeal nerve may be a key factor in the failure to appreciate abnormal parathyroid glands in this position. 3 In our series, there were five cases of ectopic glands; two of these were within the mediastinum and were accessed via a cervical incision in keeping with other published studies.…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing reoperation were distributed between SGD and MGD in a proportion similar to that of patients undergoing initial exploration, and a missed single adenoma was the leading cause of recurrent/persistent hyperparathyroidism in our group, which was in keeping with findings in the existing literature. 15,16 Given the importance of determining the probability of MGD in the setting of a potential reoperation, it is essential to include these patients in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…When carried out by an experienced surgeon (at least 10 parathyroid interventions every year), success rate is nearly 95% (1,8,16). Surgery is recommended for symptomatic patients, with renal or skeletal involvement (1,11,17).…”
Section: Treatmentmentioning
confidence: 99%